2021
DOI: 10.1038/s41598-021-97335-y
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation is associated with increased risk of lethal ventricular arrhythmias

Abstract: Atrial fibrillation (AF) is associated with various major adverse cardiac events such as ischemic stroke, heart failure, and increased overall mortality. However, its association with lethal ventricular arrhythmias such as ventricular tachycardia (VT), ventricular flutter (VFL), and ventricular fibrillation (VF) is controversial. We conducted this study to determine whether AF can increase the risk of VT, VFL, and VF. We utilized the Korean National Health Insurance Service database for this nationwide populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
2
11
1
1
Order By: Relevance
“…Notably, in our analysis, dyslipidaemia was significantly associated with a reduced risk of VT/VF/CA. While this seems anomalous, a similar finding was observed by Kim et al where a significant interaction effect was noted between AF and dyslipidaemia as well as AF and age, suggesting that younger people without dyslipidaemia were at a greater risk of VAs due to AF [12]. Whether this is a true association or if there is a further interaction effect with statin use is unclear due to the lack of data on drugs in these database-based analyses.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Notably, in our analysis, dyslipidaemia was significantly associated with a reduced risk of VT/VF/CA. While this seems anomalous, a similar finding was observed by Kim et al where a significant interaction effect was noted between AF and dyslipidaemia as well as AF and age, suggesting that younger people without dyslipidaemia were at a greater risk of VAs due to AF [12]. Whether this is a true association or if there is a further interaction effect with statin use is unclear due to the lack of data on drugs in these database-based analyses.…”
Section: Discussionsupporting
confidence: 70%
“…In the largest study evaluating the association between Vas and AF, individuals with new onset AF in the Korean general population were found to have a 4.6-fold increased risk of Vas [12]. This figure is nearly 3.5 times higher than our reported aHR of 1.34, bearing in mind our primary outcome was a composite of Vas as well as cardiac arrests as opposed to Vas only.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…A recent study reported that PACs developed due to early ventricular contractions (PVCs); subclinical AF was observed, and ischemic stroke developed due to it 23 . Conversely, another study reported that frequent PACs trigger PVCs and cause cryptogenic stroke 24 . In contrast, Engström et al identified frequent PACs as independent risk factors for stroke 25 .…”
Section: Discussionmentioning
confidence: 98%
“…Это может быть обусловлено как более высоким тонусом симпатической нервной системы, так и степенью прогрессирования кардиомиопатии с вовлечением в патологический процесс миокарда предсердий. В литературе имеются данные об ассоциации фибрилляции предсердий и повышенного риска развития ЖТ, как независимом предикторе смерти у пациентов с ЖТ [15,16].…”
Section: рис 3 кривая выживаемости Kaplan-meyer: а -риск рецидива тах...unclassified